The Relationship between Security and Online Shopping Intention - Xen, Chong Swee; Salim, Siti Aisyah (Research in Management of Technology and Business, 2020)
Online shopping has become an integral part of our daily lives as it is more convenient and easier to be done anywhere and anytime. Security is one of the major concerns that widely discussed in past studies in relation to online shopping activities. Though there are huge studies looked into security aspect of online shopping, there is still lack of studies look into context of Malaysia and focused on online shopping adoption among gen Z only. Thus, this study aims to identify the level of security towards intention of adoption among gen Z, the level of intention towards online shopping among gen Z and the relationship between security and intention of online shopping adoption among gen Z. Technology Acceptance Model (TAM) is adopted as theoretical foundation in this research. This study has collected data from 100 respondents among UTHM students. The sample was collected based on quantitative research method where self-administrated questionnaire and online survey has been applied. The data were analyzed using Statistical Package for Social Science (SPSS) software to get the demographic information, variables and the relationship between security dimensions and intention of adoption. From the analysis, it showed that the level of availability dimension toward intention of adoption among generation Z is in high range level. In term of relationship, availability dimension has a positive significant relationship towards intention of online shopping adoption with correlation coefficient of 0.476.